Korean Management, Corporate Culture, and Systems of Labour Control Between South Korea and North America - Teal, Gregory (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1995)
This paper is an attempt at synthesizing an empirical and a theoretical critique of the cultural model of industrial organization, by focussing on Korean industrial organization and industrial relations in Korea, and on a large Korean industrial organization that was based in Quebec. As a counter weight to the cultural argument, the paper shows that mechanisms established to socially integrate workers into the organization in Korea are weak, and that management has had to rely instead on authoritarianism and on the State to ensure worker compliance. The paper then presents and discusses the social organization of a Korean industrial transplant; while there was a managerial discourse of participation and diffusion of power, the gap between this discourse and the real diffusion of power was such that a sizable minority of employees did not comply with managerial objectives.